DETECTION AND COMPARISON OF SIZE OF TRICHOMONAS VAGINALIS IN DIRECT SMEAR AND CULTURE MEDIA - Muhsin E. Sulyman; Mohammed A. Kadir (Scholar Express Journals, 2021)
Objectives: Trichomonas vaginalis is one of the common human parasites among women in Iraq. It is transmitted mainly via sexual intercourse. Our aim is to compare the size of infection in direct smear and culture media. Materials & Methods: A study was carried on 250 women attending gynecology clinic in K1 hospital in North Oil Company, Kirkuk Iraq. Laboratory investigation included vaginal swabs for direct examination and culture of swabs. Results: The infection rate among women with vaginal discharge was 7 (2.8 %). The length and width of flagella and oxystyle oval and longitudinal parasite in culture media was significantly greater than in direct stained smears. The movement of parasite in culture media become sluggish after 72 hours, very weak after 96 hours and complete death after 120 hours. Conclusion: The culture media was more efficient than stained smears for detection of Trichomonas vaginalis. The size of parasite in culture media was greater than direct stained smears
Keywords: Trichomonas vaginalis; women; K1 hospital Kirkuk-Iraq